Multi-Modal Social Networks with IoT-Enabled Wearable Devices for Healthcare - Prakash, Om; Rajeev Kumar (INFOCOMP Journal of Computer Science, 2023)
The combination of wearable devices and social networking sites has led to personalized health clinics. Since people are connected, their health is also interconnected. The COVID-19 pandemic has shown how important it is to use social media and wearable devices to track, listen to, interact with, and share important health information. By measuring the user’s activity, stress, blood pressure, body temperature, etc., these techniques are always making healthcare better. This research proposes a framework to develop a standardized system using wearable devices and social media platforms for healthcare that will focus on detecting and monitoring chronic diseases like BP, diabetes, mental health, etc. The proposed framework works efficiently on two different interrelated datasets with appreciable accuracy.